Evaluation of an Emergency Department Sexually Transmitted Infection Empiric Treatment and Linkage-to-care Program - Victoria R. Bortner; Emily Holbrook; Heather Henderson; Jason W. Wilson (Western Journal of Emergency Medicine)
Introduction: Rates of sexually transmitted infections (STI), remain high in Hillsborough County, FL. As the emergency department (ED) is frequently used for STI diagnosis and treatment, a local hospital ED implemented a linkage-to-care program using a callback system to ensure that patients with chlamydia, gonorrhea, and/or syphilis received treatment. Our primary aim in this paper was to evaluate implementation of an ED-based STI treatment program by describing empiric, follow-up, and overall treatment rates in STI-positive patients by disease and sex. A secondary aim was to evaluate reasons for undertreatment during the acute-care encounter. Methods: We conducted this quality assurance project, including a retrospective chart review of electronic health records from 2019–2022, at an urban ED in Hillsborough County, Florida. During this period, we reviewed all records reflecting positive results for chlamydia, gonorrhea and/or syphilis to determine whether empiric treatment was administered in the ED or the patient required coordination for follow-up care. Patients who received empiric treatment or successful follow-up treatment were classified as treated, while those who did not receive successful follow-up treatment were classified as untreated. Results: A total of 1,170 patients were diagnosed with an STI at an urban, quaternary-care hospital in the county. Of these, 689 (58.9%) had chlamydia, 324 (27.7%) had gonorrhea, 133 (11.4%) had dual gonorrhea-chlamydia, and 24 (2.1%) had syphilis. Rates of STI empiric, follow-up, and overall treatment were 47.1%, 86.1%, and 92.6%, respectively. Empiric and overall treatment rates were highest for male patients (72.3% male, 33.4% female) and patients presenting with gonorrhea (67.6% gonorrhea, 63.9% chlamydia). Follow-up treatment rates were highest for female patients (87.1%) and patients presenting with gonorrhea (87.6%). Conclusion: Our findings emphasize both the successes and opportunities for improvement of a linkage-to-care protocol to provide treatment access for patients in the ED who test positive for sexually transmitted infections. Given the significant strain on the public health infrastructure in the United States and on our local Department of Health, ED-based linkage programs fill an important gap in healthcare delivery. Going forward, improving overall treatment rates in females and patients with chlamydia or syphilis is warranted.